HUBUNGAN ANTARA JIWA WIRAUSAHA MAHASISWA DENGAN MOTIVASI, LINGKUNGAN KELUARGA DAN PENDIDIKAN PADA POLITEKNIK LP3I JAKARTA KAMPUS BEKASI - Darmawan Darmawan; Jajang Setiawan (POLITEKNIK LP3I JAKARTA, 2017)
ABSTRACT Today, the growth of economic level begins to rise again that is generated by the increase of different kind of product and different kind of businesses that are offered by both individual businesses that are done easly independently. To deal with all of business trends, the education institution has to prepare the students to be able to set up a business idenpendedntly through the subject of entrepeuneurship. As it is regulated in Vision and Mision of study program and is also regulated in the curriculum of lectures. This research is aimed at to find out the correlation between the spirit of entrepeunership and motivation , Family background, and education level. Based on the research result, the finding showed that the spirit of entrepeneurship correlated with the motivation and family background. Based on the finding, it was also found that education level did not correlate with that the spirit of entrepeneurship. In regard with the findings, it is important to develop more the motivation of students to touch up the sperit of entrepenuership. Key words: Entrepenuer, Students, Entrepeuneurship.